A failure of imagination: Competing narratives of 9/11 truth. (November 2015) - Fenster, Mark
This essay describes the emergence of the 9/11 attacks on the World Trade Center and Pentagon as an object of conspiratorial intrigue and imagination, offering a snapshot of the "9/11 truth movement" and its various theories as they began to reach full bloom. Theories about the attacks have come to constitute the dominant conspiratorial present – a present that looks remarkably like the mid- and late-twentieth-century past, despite significant changes in information technology and the continuing institutionalization and ironization of conspiracy theory as an influential form of popular politics. In addition to the 9/11 conspiracy community, the essay considers the battle over the 9/11 Commission's review of the government's failure to anticipate the terrorist attacks. The Commission engaged in knowing and savvy efforts to respond to conspiracy theories and to preempt popular belief in them, offering an authoritative narrative (or, more precisely, set of narratives) to explain what occurred. Meanwhile, the 9/11 truth movement made equally knowing and savvy efforts to critique the official account, responding with its own efforts to reinterpret and re-narrate the attacks, their causes, and what they signify about the contemporary world. While the 9/11 Commission may have criticized the federal government and its intelligence services for their failures of imagination prior to the attacks, the truth movement criticized the Commission either for a failure of imagination – an explanation for the attacks that could see through the "official" account – or for a quite imaginative cover-up of the hidden truths of 9/11. By considering the clash between official authorities and an active conspiracy community, this essay considers how the movement attempted to form a collective political and scholarly community, producing a blizzard of texts offering narratives that compete with the ones told by the Commission that seek the impossible grail of conspiracy theory: the truth. The essay also considers the effects, if any, of the state's attempt to preempt and respond to conspiracy theories.